Effect of Activity-Based and Challenge-Based Learning Approaches on Technical Colleges Students’ Psychomotor Achievement in Furniture Craft Technology - Abdullahi Muhammad Hassan; Abdullahi Shaba Mohammed (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
This study adopted the quasi-experimental research design, precisely, pre-test, post-test nonequivalent control group design. The population for the study was 210 National Technical Certificate (NTC II) furniture craft technology students (175 males and 35 females) in Technical Colleges. This study was carried out in Zamfara and Katsina State. The analysis was guided by three research questions and three hypotheses at 0.05 level of significance. The data were obtained with Furniture craft technology Cognitive Achievement Test (FTCAT) and Furniture craft technology Interest Inventory (FTII). The lesson plan, FTCAT, and FTII were subjected to face and content validation by three experts. The instrument was trial tested on a sample of 22 NTC II furniture craft technology students of Government Technical College FCT-Abuja. Kuder-Richardson 20(K-R20) and the Pearson product-moment correlation coefficient were utilized to establish the coefficient of internal consistency and stability of the FTCAT. The values were found to be 0.72 and 0.81 respectively. Data obtained from the administration of the instrument was examined with mean to answer the research questions and Analysis of Covariance (ANCOVA) statistic was used to test the hypotheses. The results showed that the Challenge-based learning approach is more successful in enhancing the students' achievement in furniture craft technology than the Activity-based learning approach. It was recommended that the Ministry of Education and National Board for Technical Education (NBTE) should organize workshops, seminars and in-service training for technical teachers regularly